1998
DOI: 10.1016/s1097-2765(00)80164-1
|View full text |Cite
|
Sign up to set email alerts
|

Histone-like TAFs Are Essential for Transcription In Vivo

Abstract: In yeast, the TBP-associated factors (TAFs) Taf17, Taf60, and Taf61(68) resemble histones H3, H4, and H2B, respectively. To analyze their roles in vivo, conditional alleles were isolated by mutagenizing their histone homology domains. Conditional alleles of TAF17 or TAF60 can be specifically suppressed by overexpression of any of the other histone-like TAFs. This and other genetic evidence supports the model of a histone octamer-like structure within TFIID. Shifting strains carrying the conditional TAF alleles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
121
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(133 citation statements)
references
References 36 publications
10
121
0
2
Order By: Relevance
“…Surprisingly, we did not isolate any other TAF II genes in our screen, including the histone-like TAF60 or TAF17. A previous report shown that overexpression of TAF68/61, TAF60 or TAF17 suppressed mutations in TAF60 or TAF17, but failed to show the reciprocal result that overexpression of other histone-like TAF II s can suppress a TAF68/61 mutant (Michel, 1998). It is possible that the suppression phenotypes caused by the overexpression of other histone-like TAF II genes were too subtle to be identified in our initial screen.…”
Section: Isolation Of High Copy Suppressors Of the Taf68-9 Mutantmentioning
confidence: 82%
See 1 more Smart Citation
“…Surprisingly, we did not isolate any other TAF II genes in our screen, including the histone-like TAF60 or TAF17. A previous report shown that overexpression of TAF68/61, TAF60 or TAF17 suppressed mutations in TAF60 or TAF17, but failed to show the reciprocal result that overexpression of other histone-like TAF II s can suppress a TAF68/61 mutant (Michel, 1998). It is possible that the suppression phenotypes caused by the overexpression of other histone-like TAF II genes were too subtle to be identified in our initial screen.…”
Section: Isolation Of High Copy Suppressors Of the Taf68-9 Mutantmentioning
confidence: 82%
“…Unexpectedly, initial studies revealed that the mutation or depletion of seven TAF II s individually resulted in gene-specific defects, and not global reductions in transcription Moqtaderi et al, 1996;Walker et al, 1996). In contrast, genetic analysis of other TFIID subunits that have sequence similarities to the core histones has shown that they are required for the transcription of a larger number of genes (Apone et al, 1998;Holstege et al, 1998;Michel et al, 1998;Moqtaderi et al, 1998;Natajaran et al, 1998;Sanders et al, 1999;Reese et al, 2000). The interpretation of these results is complicated by the presence of certain TAF II s in the SAGA histone acetyltransferase complex (Grant et al, 1998), and their function in multiple complexes may partially explain the expanded requirement for these TAF II s in transcription (Lee et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This core structure was suggested to depend upon the HFD, a structural motif shared by the core histones (22) and many other proteins (70). Nine of 14 yeast Tafps appear to contain HFDs, and subsets of these can form dimers with specific partner HFD Tafps (3,6,9,23,24,29,45,47,80). Indeed, Tan and colleagues (66) have described the formation and characterization of such an octameric complex comprised of four HFD-Tafps, a dimer of Taf6p-Taf9p bound to a dimer of Taf4p-Taf12p.…”
mentioning
confidence: 99%
“…Not only are TAF II s components of transcription factor TFIID, but distinct subsets of TAF II s are also components of the SAGA, PCAF, and TFTC complexes (13,14,21,31,40). For human TFIID (hTFIID), cDNAs for 11 hTAF II s have been characterized (10,16,18,24,25).Genetic and biochemical experiments show that some TAF II s are important for promoter recognition and expression of a subset of promoters (15,38,39), while others are more generally required for transcription in Saccharomyces cerevisiae (2,26,27,29 Expression of hTAF II 28 also potentiates ligand-dependent activation by the AF-2s of many NRs, the most dramatic effects being seen with the receptors for 9-cis retinoic acid (retinoid X receptor), estrogen (estrogen receptor [ER]), and the VDR (22). Deletion analysis showed that coactivator activity required amino acids 150 to 179 in the C-terminal domain of hTAF II 28.…”
mentioning
confidence: 99%
“…Genetic and biochemical experiments show that some TAF II s are important for promoter recognition and expression of a subset of promoters (15,38,39), while others are more generally required for transcription in Saccharomyces cerevisiae (2,26,27,29). An increasing body of results also shows that hTAF II 28, hTAF II 135, and hTAF II 105 can act as specific transcriptional coactivators in mammalian cells.…”
mentioning
confidence: 99%